The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1038/nrg3461
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropy in complex traits: challenges and strategies

Abstract: Genome-wide association studies have identified many variants that each affects multiple traits, particularly across autoimmune diseases, cancers and neuropsychiatric disorders, suggesting that pleiotropic effects on human complex traits may be widespread. However, systematic detection of such effects is challenging and requires new methodologies and frameworks for interpreting cross-phenotype results. In this Review, we discuss the evidence for pleiotropy in contemporary genetic mapping studies, new and estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
955
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 955 publications
(1,000 citation statements)
references
References 132 publications
13
955
1
4
Order By: Relevance
“…Recent studies have demonstrated widespread pleiotropy: genetic loci that simultaneously influence related and sometimes seemingly unrelated traits. 34 Integrating pleiotropic information to jointly predict related traits has shown promise. 35 Extending XP-BLUP to leverage both trans-ethnic and cross-trait information may be particularly useful for under-studied traits.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated widespread pleiotropy: genetic loci that simultaneously influence related and sometimes seemingly unrelated traits. 34 Integrating pleiotropic information to jointly predict related traits has shown promise. 35 Extending XP-BLUP to leverage both trans-ethnic and cross-trait information may be particularly useful for under-studied traits.…”
Section: Discussionmentioning
confidence: 99%
“…Such pleiotropic effects have been demonstrated across several psychiatric disorders (Solovieff et al, 2013). For example, a recent study that examined schizophrenia (SCZ), bipolar disorder (BPD), MDD, and attention-deficit/hyperactivity disorder (ADHD) found that SNP-based heritability ranged from 17 to 29% within disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The former is known as biological pleiotropy, whereas the latter is a type of spurious pleiotropy (Solovieff et al, 2013). In this study, we investigated the genetic background of relationships between immunity and growth not only from the view of biological pleiotropy and spurious pleiotropy but also with the idea that genes that are involved in the same pathway could interact with one another, which can be regarded as another type of pleiotropy -namely, mediated pleiotropy (as reviewed by Solovieff et al, 2013).…”
Section: Introductionmentioning
confidence: 99%